Diversity, activity analysis and effectivity of rhizobacteria in plants rhizosphere on the growth of Arachis hypogaea L plants - Sri Purwaningsih (The East Java Biological Society, 2018)
This research was conducted to observe the diversity, activity analysis and effectivity of rhizobacteria in plant rhizosphere on the growth of Arachis hypogaea L plants. The soil samples were collected from rhizosphere soil from different plants at Suro Muncang village and Bukit Peninjauan village. The rhizobacteria was isolated in YEMA media to test the qualitative activity including nitrogen, indole acetic acid (IAA) fixation, and siderophores. An isolate used in this research were 1 RB, 2 RB, 8 RB, 9 RB, 10 RB, 11 RB, 16 RB, 17 RB, 19 RB, 20 RB, 21 RB. Experimental plants were harvested after 45 days. The parameters used were the dry weight of shoots, roots, nodules root, total plants, number of nodules, and symbiotic capacity. The research design was conducted by Completely Randomized Design with three replications per treatment. The results showed that the population of rhizobacteria ranged between 13-51 x 105 CFU/g soil. Rhizobacterial isolates showed different level of plant growth promotion, which is the isolate 19 RB (isolate from Leucaena leucacephala plant) has a higher influence to the growth of A. hypogaea L.